MAKSIM KERJA SAMA KUANTITAS DAN PENYIMPANGANNYA DALAM FILM JAWA WOKO CHANNEL “BONDO NEKAT” - Prihartini, Indah Dwi; Maharani, Aulia (Universitas Negeri Surabaya, 2024)
ABSTRACT The use of everyday language shows that language is an important part of communication, one of which is the language in the short film